Lightning performance of power lines - comparison of calculated and observed data; 21st International Conference on Lightning Protection - ICLP'92, Berlin, Germany, September 22 - 25, 1992 - Dulzon A. A. Alfred Andreevich (1992, 1992)
В фонде НТБ ТПУ отсутствует